Assessment of grapevine germoplasm collection for resistance to grape leaf rust (Phakopsora euvitis) using a leaf disc assay - Gomes B.R.* (2019)
© 2019, Springer Nature B.V.The present study aimed to assess 25 grapevine genotypes, representing different Vitis species, for resistance to grapevine leaf rust (GLR), caused by Phakopsora euvitis, using leaf disc assay. Disinfected leaf discs of 12 mm in diameter were placed in agar-water medium. On the abaxial side, a 30-µl drop at a concentration of 30,000 urediniospores/ml was deposited and incubated in a growth chamber under controlled conditions. The genotypes were assessed by the components of resistance latent period, number of pustule per cm2, diameter of pustules (DP; mm), number of urediniospores per disc, severity (%), and area under the disease severity progress curve. The ANOVA revealed a significant difference (p < 0.05) among genotypes for all components of resistance tested. Significant correlation was observed for all components of resistance evaluated. Based on disease severity, the genotypes were classified into four resistance categories: (1) resistant, (2) partially resistant, (3) susceptible, and (4) highly susceptible. None of the genotypes were asymptomatic and 32% were considered resistant or partially resistant. ‘IAC766’ and ‘Seibel 405’ were the most resistant, showing the lowest severity of 0.03 and 1.48%, respectively. ‘Seibel 128’, V. del rioi Sd1, V. slavinii and V. candicans were partially resistant. From the resistant and partially resistant genotypes, only V. candicans has trichomes on the abaxial leaf surface. Particularly, the resistant genotypes are resistance sources to GLR to be explored in future breeding programs and for genetic analysis to localize resistant genes to P. euvitis.